The competencies of newly qualified psychiatric nurses - Lunice B Khoza; Valerie J Ehlers (AOSIS, 2000)
This research report comprises part of a larger study, which endeavoured to identified the competencies of newly qualified nurses (NQNs) as viewed by senior professional nurses (SPNs) in the clinical units. This report concentrates only on the competencies of the NQNs working in the psychiatric nursing units. SPNs (N=29) from certain health services in the Northern Province (NP) of the RSA, constituted the population for this research. A descriptive survey was used as a research approach to conduct this research. The fieldwork, entailing the distrib~ltiona nd collection of the questionnaires by a researcher, was done during a period of political and labour unrest in this area. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.